A first-principles study on the chemical stability of inorganic perovskite solid solutions Cs1−xRbxPbI3 at finite temperature and pressure. Issue 37 (6th September 2018) - Jong, Un-Gi; Yu, Chol-Jun; Kye, Yun-Hyok; Kim, Yun-Sim; Kim, Chol-Ho; Ri, Son-Guk
Abstract : The inorganic halide perovskite Cs(Rb)PbI3 has attracted significant research interest for its application as a light-absorbing material in perovskite solar cells (PSCs). Abstract : The inorganic halide perovskite Cs(Rb)PbI3 has attracted significant research interest for its application as a light-absorbing material in perovskite solar cells (PSCs). Although there have been extensive studies on structural and electronic properties of inorganic halide perovskites, the investigation on their chemical stability is lacking. Therefore, we investigate the effect of substituting Rb for Cs in CsPbI3 on the chemical stability against decomposition using first-principles thermodynamics. The calculated Helmholtz free energy of solid solutions indicates that Cs1− x Rb x PbI3 has good thermodynamic stability at room temperature due to the good miscibility of CsPbI3 and RbPbI3 . By calculating the Helmholtz free energy difference of solid solutions Cs1− x Rb x PbI3 from their constituents Cs1− x Rb x I and PbI2, we find that the Rb content x ≈ 0.7 and 0.4 at zero and room temperature are the turning points, at which the chemical decomposition changes from endothermic to exothermic. From the calculated Gibbs free energy differences, we further highlight that RbPbI3 may decompose spontaneously at any temperature and pressure, while CsPbI3 in the cubic phase can be safe against decomposition in the temperature range of 0–600 K and the pressure range of 0–4 GPa. Our work reasonably explains the experimental observations and paves the way for understanding the chemical stability of inorganic halide perovskites and designing efficient inorganic halide PSCs.